2018
DOI: 10.1186/s40608-018-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Television exposure and overweight/obesity among women in Ghana

Abstract: BackgroundAlthough the public health importance of the association between television (TV) viewing and obesity and/or related outcomes have been demonstrated in both cross-sectional and prospective studies elsewhere, similar studies are lacking within the African region. With the view to fill this gap in the literature, the current study explored the association between TV exposure and overweight/obesity among Ghanaian women.MethodsBased on a sample of 4158 women, descriptive statistics and binary logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…60 Access to latrine was also a significant predictor, indicating that promoting hygiene could improve child's health. 61 Finally, like our study, Tuoyire 62 found that TV viewing is a contributing factor of obesity, possibly because mothers who had TV in their households inherently spent a lot of time viewing TV in place of engaging in physical activities, resulting in an overall decrease in energy expenditure.…”
Section: Discussionsupporting
confidence: 57%
“…60 Access to latrine was also a significant predictor, indicating that promoting hygiene could improve child's health. 61 Finally, like our study, Tuoyire 62 found that TV viewing is a contributing factor of obesity, possibly because mothers who had TV in their households inherently spent a lot of time viewing TV in place of engaging in physical activities, resulting in an overall decrease in energy expenditure.…”
Section: Discussionsupporting
confidence: 57%
“…We found higher education and working status to be constantly associated with overweight/obesity in 2005 and 2015 and not in 2010/11. Studies elsewhere concur with current findings [18]. This could be related to the fact that these highly educated women are more likely to be working and more likely to come from richer households, and thus use energy saving devices at home to execute their daily domestic chores or can afford to employ domestic workers.…”
Section: Discussionsupporting
confidence: 86%
“…This is contrary to other studies which found asset ownership such as radio and telephone to be associated with obesity. It is not surprising that a sedentary lifestyle has been observed to closely relate to time spent watching television as a leisure activity [13,18]. Subsequently, reduced energy expenditure because of this leisure activity is closely associated with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately increases their risk of gaining excessive body weight 15 16. Television watching is also associated with an increase in energy intake, which may sometimes be attributable to their frequent exposure to television advertisements of food and beverages and the subsequent consumption of the said food and beverages 17–21…”
Section: Introductionmentioning
confidence: 99%